2016
DOI: 10.1016/j.rboe.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of patellar height methods in the Brazilian population

Abstract: ObjectiveThe methods most used for patellar height measurement were compared with the plateau–patella angle method.MethodsA cross-sectional study was conducted, in which lateral-view radiographs of the knee were evaluated using the three methods already established in the literature: Insall–Salvati (IS), Blackburne–Peel (BP) and Caton–Deschamps (CD). These were compared with the plateau–patella angle method. One hundred and ninety-six randomly selected patients were included in the sample.ResultsThe data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This finding is consistent with previous studies conducted in different populations, such as Oladrin et al 7 who analyzed the patellar morphology of South Africans of European ancestry and reported similar findings. [15][16][17] The results of the present study have important clinical implications. For instance, the findings could be used to inform surgical procedures such as patellar resurfacing, total knee arthroplasty, and patellar realignment surgery.…”
Section: Discussionmentioning
confidence: 86%
“…This finding is consistent with previous studies conducted in different populations, such as Oladrin et al 7 who analyzed the patellar morphology of South Africans of European ancestry and reported similar findings. [15][16][17] The results of the present study have important clinical implications. For instance, the findings could be used to inform surgical procedures such as patellar resurfacing, total knee arthroplasty, and patellar realignment surgery.…”
Section: Discussionmentioning
confidence: 86%
“…6,8,15,18,19 Lateral radiographic studies of the knee in 30°and 90°fl exion demonstrated dissimilarities between IS and CD indexes on the same joint without suggesting a clear aetiology as to why such a difference between measurements exists. 20,21 A suspicion is that anatomical variations could disrupt measurements, affect indexes and alter results, such as morphological variations of the patella (i.e. long-nosed) can influence the reference points used to determine the Insall-Salvati ratio and a patella Alta can be misdiagnosed as normal.…”
Section: Tablementioning
confidence: 99%
“…In dogs, radiographic evaluation of the patellar height was performed using several indices well-known in human medicine, eg the (modified) Insall-Salvati index, Blackburne-Peel index or de Carvalho index [1][2][3][4][5][6][7]. The tibia plateau-patellar angle (TPPA) is a simple diagnostic tool from Portner and Pakzad (2011) used in humans and dogs [7,[9][10][11][12][13][14][15][16]. To eliminate index calculations, this method only requires a single angle measurement without additional calculation.…”
Section: Introductionmentioning
confidence: 99%